A Precocious End of Innocence: Re-reading Children's Literature for Today (Altre Modernità, 2010)
A Precocious End of Innocence: Re-reading Children's Literature for Today(Laura Tosi (ed.), Hearts of Lightness: the Magic of Children's Literature, Venezia, Cafoscarina, 2001, p.197 ISBN88-88613-18-8)by Nicoletta Vallorani